Diagnostic de l’échec de la contractualisation des mesures agri-environnementales pour réduire les incursions des Flamants dans les rizières de Camargue (France) - Lisa Ernoul; François Mesléard; Arnaud Béchet (VertigO)
Flamingo forays in the Camargue rice fields only affect a small percentage of the surface area ; however, the damage incurred in the individual fields can be important and may even require the entire area to be replanted. Previous research has demonstrated hedges around rice fields could reduce the attractiveness of the fields for flamingos. In consequence, Agri-environmental Schemes (AES) were proposed to compensate farmers for hedge maintenance. These AES have not been contracted in great numbers and few new hedges have been established in the study area. We demonstrate that the lack of contractualisation can be explained by several factors : the administrative limits of the AES, the poor financial compensation for the measures and the perceived incompatibility of hedges with current agricultural practices. In order to promote the landscape changes necessary to reduce flamingo forays, we propose that the current AES be extended to cover the territory affected by the incursions and be reformulated to take into consideration the time and effort necessary for farmers to produce these changes. The AES alone may not be sufficient and a pilot farmer approach linked to AES could be a possible tool to spur the change in practices required in the Camargue.